Understanding the continuum of radionecrosis and vascular disorders in the brain following gamma knife irradiation: An MRI study. Issue 4 (10th November 2016) - Constanzo, Julie; Masson‐Côté, Laurence; Tremblay, Luc; Fouquet, Jérémie P.; Sarret, Philippe; Geha, Sameh; Whittingstall, Kevin; Paquette, Benoit; Lepage, Martin
Abstract : Purpose: The radiation dose delivered to brain tumors is limited by the possibility to induce vascular damage and necrosis in surrounding healthy tissue. In the present study, we assessed the ability of MRI to monitor the cascade of events occurring in the healthy rat brain after stereotactic radiosurgery, which could be used to optimize the radiation treatment planning. Methods: The primary somatosensory forelimb area (S1FL) and the primary motor cortex in the right hemisphere of Fischer rats (n = 6) were irradiated with a single dose of Gamma Knife radiation (Leksell Perfexion, Elekta AG, Stockholm, Sweden). Rats were scanned with a small‐animal 7 Tesla MRI scanner before treatment and 16, 21, 54, 82, and 110 days following irradiation. At every imaging session, T 2 ‐weighted ( T 2 w), Gd‐DTPA dynamic contrast‐enhanced MRI (DCE‐MRI), and T 2 * ‐weighted ( T 2 * w) images were acquired to measure changes in fluid content, blood vessel permeability, and structure, respectively. At days 10, 110, and 140, histopathology was performed on brain sections. Locomotion and spatial memory ability were assessed longitudinally by behavioral tests. Results: No vascular changes were initially observed. After 54 days, a small necrotic volume in the white matter below the S1FL, surrounded by an area presenting significant vascular permeability, was revealed. Between 54 and 110 days, the necrotic volume increased and was accompanied by the formation of a ring‐like region, where a mixture of necrosis and permeable blood vessels were observed, as confirmed by histology. Behavioral changes were only observed after day 82. Conclusion: Together, DCE‐MRI and T 2 * w images supported by histology provided a coherent picture of the phenomena involved in the formation of new, leaky blood vessels, which was followed by the detection of radionecrosis in a preclinical model of brain irradiation. Magn Reson Med 78:1420–1431, 2017. © 2016 International Society for Magnetic Resonance in Medicine.